EU Law on Food Naming: The prohibition against misleading names in an internal market context - Mette Ohm Rørdam (Copenhagen Business School (CBS), 2013)
This thesis investigates how food naming is regulated in the European Union with the aim to structure and explain the different rules regulating food naming and the interactions between the different rules, thereby clarifying de lege lata. Further, the thesis sets out to determine to what degree the Member States within the EU are free to regulate the naming of imported as well as domestically produced food, by way of legislation and/or by enforcement of the prohibition against misleading names. The interaction between the prohibition against misleading names and the obligation to mutually recognise names which have been legally used in other Member States are central in this thesis. The first part of the thesis introduces the thesis subject and provides an explanation to the approaches taken. The empirical data used for identifying practical real-life cases concerning potentially misleading names is presented. The second part of the thesis elaborates on the various EU rules in secondary law, their scope and objectives, including an examination of the rationales behind the rules based on application of economic theory. The borderlines between the rules are clarified. Part three of the thesis contains legal dogmatic analyses and discussions of the different EU rules regulating food naming. The analyses of the rules are based on practical real-life cases in which food naming has shown to be a challenging task. The difficulties addressed relate to: precision of names (the task of finding a name precise enough to provide adequate information to consumers without narrowing the product's competitive field); product identity (difficulties in naming products that refer to specific ingredients and in which traditional ingredients have been replaced); the use of geographical names (which potentially mislead consumers) and language difficulties. In the last chapter of part three an analysis is provided of the concept of fairness and general prohibition against misleading consumers in order to clarify the criteria for applying these in real-life cases. Despite the existence of rather detailed rules on naming and labelling of food, which provides clarity in relation to food naming, the application of these rules is dependent on consumers' expectation and potentially deception which must be assessed on a case-by-case basis, whereby the predictability of the rules is weakened. Part four of the thesis focuses on the borderlines between primary and secondary EU law and on answering the second part of the research question. Primary EU law defines the fundamental borderlines for EU law on food names and limits how food legislation can and must be applied. First part of this analysis focuses on the naming of imported food products, while the second part focuses on the naming of domestically produced food. The relevant sources of law are analysed and discussions are provided. It is concluded that the principle of mutual recognition takes precedence over the prohibition against misleading names, which prevents Member States from regulating the naming of imported food, by way of legislation and by enforcement of the prohibition against misleading names. Secondary EU law also limits how Member States can regulate the naming of domestically produced food. Part five provides the conclusion to the research question.
hdl:10398/8670
Keywords: 650